Teaching competency in virtual education: Systematic review - Martha-Amparo Cuzcano-Huarcaya; Juan Mendez Vergaray; Carol Maritza Cuzcano-Santa Cruz; Sebastian Sanchez Diaz; Edward Flores (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study arises as a need to recognize teaching competencies and their integration to become professionals who respond to current challenges aimed at improving learning achievements and comprehensive training of students. The objective of the research was to analyze and recognize teaching competencies in virtual education in higher education students. The study is important due to the direct relationship with student learning. The study was qualitative research, with a systematic design, followed the methodology proposed by the PRISMA declaration. Inclusion and exclusion criteria were applied to process the articles analyzed. A study was conducted based on 38 articles published in high impact scientific journals between 2019 and 2022. The results showed that teaching competencies in virtual education must be worked in an integrated manner: disciplinary, pedagogical, technological and research competencies that will translate into a real development of teaching-learning processes, better teaching performance and student performance. The studies determine that the disciplinary, pedagogical, technological, and investigative competence must be worked on in an interrelated manner, there is a need to integrate technology effectively, and it is important to promote research in students through experiments that allow building skills.